Domestic Application of the ECHR : Courts As Faithful Trustees - Bjorge, Eirik, 1983- (Oxford, United Kingdom : Oxford University Press, 2015)
A critique of how domestic courts in the EU apply the European Convention on Human Rights and interact with the European Court of Human Rights at Strasbourg. It considers the British, French, and German approaches to the ECHR and shows that domestic courts apply and develop the Convention faithfully and positively.
Includes bibliographical references and index.
Keywords: European Court of Human Rights; European Court of Human Rights; Convention for the Protection of Human Rights and Fundamental Freedoms -- (1950 November 5); Convention for the Protection of Human Rights and Fundamental Freedoms; Conflict of laws -- Jurisdiction -- Europe; International law and human rights -- Europe; Human rights -- Europe; Conflict of laws -- Jurisdiction; Human rights; International law and human rights; Law - Europe, except U.K.; Law - Non-U.S.; Law, Politics & Government; Europe